2021
DOI: 10.1186/s12888-021-03297-w
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of internet-based cognitive behavioural therapy for depression and anxiety among Arabic-speaking individuals in Sweden: a qualitative study

Abstract: Background Internet-delivered cognitive behavioural therapy (ICBT) is a promising treatment for refugee and immigrant populations suffering from common mental disorders. The aim of the present study was to investigate experiences of participating in a guided ICBT program among resettled Arabic-speaking individuals suffering from symptoms of anxiety and depression. Methods Ten individuals who had previously received ICBT consented to participate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 58 publications
(103 reference statements)
1
46
0
Order By: Relevance
“…It is also possible that psychosocial stress, such as the uncertainty regarding permanent residence permits currently faced by many Afghan youths ( Swedish National Board of Health and Welfare, 2019 ), could interfere with participation in the trial. Qualitative findings support this, and it is also identified as a factor that can influence adherence and engagement with treatments in previous studies targeting migrants and refugees ( Djelantik et al, 2020 ; Lindegaard et al, 2021 ). Finally, it is also possible that the education level of the participants acted as a barrier to engaging with the treatment in some way.…”
Section: Discussionsupporting
confidence: 79%
“…It is also possible that psychosocial stress, such as the uncertainty regarding permanent residence permits currently faced by many Afghan youths ( Swedish National Board of Health and Welfare, 2019 ), could interfere with participation in the trial. Qualitative findings support this, and it is also identified as a factor that can influence adherence and engagement with treatments in previous studies targeting migrants and refugees ( Djelantik et al, 2020 ; Lindegaard et al, 2021 ). Finally, it is also possible that the education level of the participants acted as a barrier to engaging with the treatment in some way.…”
Section: Discussionsupporting
confidence: 79%
“…Four studies (Campos et al, 2019;Choi et al, 2012;Lin et al, 2020;Lindegaard et al, 2019) utilized structured clinical interviews. Several other studies relied on self-report measures (A. L. M. Andrade et al, 2016;Bramley et al, 2005;Caplan et al, 2020;Dahne et al, 2019;Eylem et al, 2021;Harper Shehadeh et al, 2020;Knaevelsrud et al, 2015;Lindegaard et al, 2021;Menezes et al, 2019;Muñoz et al, 2009Muñoz et al, , 2016Osilla et al, 2015;Salamanca-Sanabria et al, 2020) and some based eligibility on treatment-seeking (Muroff et al, 2017 andTiburcio et al, 2018). Five studies appeared to develop DMHIs that were more preventative in nature, including Arevian et al 2021)'s DMHI, which aimed to reduce stress and improve well-being among Black Americans.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…Participants in the majority of studies (n = 16, 80%) indicated generally positive attitudes towards, satisfaction with, and willingness to recommend DMHIs. Two studies reported low acceptability (Eylem et al, 2021;Lindegaard et al, 2021), as operationalized by high dropout rates and/or minimal adherence. Participants found DMHIs delivered through each modality (mobile application, web-based, and text-based) to be acceptable, although no study directly compared satisfaction across modality.…”
Section: Acceptabilitymentioning
confidence: 99%
“…Furthermore, the intervention was developed as a brief, psychoeducative health promotion intervention, not comprising recommended and effective components of sleep treatment that require high self-motivation and are demanding for users (e.g., sleep restriction and stimulus control) ( 94 ). This approach was chosen because the primary goal of the intervention was to provide refugees with initial access to healthcare, to be followed by more intensive treatment for sleep disturbances or other mental health conditions ( 37 , 95 , 96 ).…”
Section: Discussionmentioning
confidence: 99%